2005
DOI: 10.1164/rccm.200402-230oc
|View full text |Cite
|
Sign up to set email alerts
|

Decline in Lung Function in the Busselton Health Study

Abstract: Asthma in adults may be associated with chronic airflow obstruction, possibly resulting from airway disease in early life and/or a greater rate of decline in lung function in adult life compared with those with asthma. Treatment and cigarette smoking may also influence the rate of decline of lung function. The aim of this analysis was to examine the level and rate of decline in lung function in relationship to asthma and cigarette smoking in adults. Subjects (n = 9,317) had participated as adults (> 18 years) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
257
5
12

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 373 publications
(300 citation statements)
references
References 31 publications
18
257
5
12
Order By: Relevance
“…Participants The BHS includes a series of seven crosssectional population health surveys of adult residents of the Shire of Busselton in the south-west of Western Australia, undertaken between 1966 and 1990, and focused on respiratory and cardiovascular phenotypes [23][24][25]. In 1994/1995 a cross-sectional community follow-up study, which included the collection of blood for DNA extraction, was undertaken of all survivors of previous surveys.…”
Section: Methodsmentioning
confidence: 99%
“…Participants The BHS includes a series of seven crosssectional population health surveys of adult residents of the Shire of Busselton in the south-west of Western Australia, undertaken between 1966 and 1990, and focused on respiratory and cardiovascular phenotypes [23][24][25]. In 1994/1995 a cross-sectional community follow-up study, which included the collection of blood for DNA extraction, was undertaken of all survivors of previous surveys.…”
Section: Methodsmentioning
confidence: 99%
“…Lung function progressively declines with aging (James et al, 2005) and can lead to the development of obstructive lung diseases (OLDs), such as asthma and chronic obstructive pulmonary disease (COPD), which represent a significant and increasing global health problem (Buist et al, 2007). Several studies have also shown that low or declining lung function, measured by forced expiratory volume in one second (FEV 1 ) or forced vital capacity (FVC), is a strong predictor of all-cause (Hole et al, 1996) and cardiovascular mortality (Tockman et al, 1995;Schroeder et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The factors leading to lung function decline with age are not well understood (James et al, 2005). Both smoking and asthma accelerate lung function decline (James et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presented patient did not develop frequent exacerbations, but there was 240 mL reduction in post‐bronchodilator FEV 1 over 4 years (−60 mL/year) after 1.5 year of treatment, suggesting a rapid decline in lung function compared with annual rate of decline in Asian COPD patients. This rapid rate of decline in FEV 1 might be due to the combination of asthma and smoking [6]. Prospective longitudinal studies are necessary to assess the natural course of ACOS with optimal interventions.…”
Section: Discussionmentioning
confidence: 99%